THE INFLUENCE OF ROMANCE TOWARD TEACHING AND LEARNING PROCESS AT THE THIRD SEMESTER STUDENTS OF GUNUNG RINJANI UNIVERSITY IN ACADEMIC YEAR 2017/2018 - RASYID RIDHO HAMIDY (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2020)
The purposes of this research are: 1) to know the factors that cause the students adopting the romance, 2) to know the influence of romance toward teaching and learning process. The subjects of this research is the third semester students of Gunung Rinjani University in Academic Year 2017/2018. This research used qualitative approach, with the data were in the form of interviews result of respondents after conducting observation. To collect the data were analyzed using Miles and Huberman’s model of analysis that consisting of data reduction, data display and conclusion.Data analysis shows that: 1) factors causing the students to adopt the romance: internal factors consisting of the lake provision of religious understanding, uncontrolled lust, catching personal problems and faulty solution, puberty fluctuation, and the external factors consist of poor environment and bad friends, 2) the influence of romance in the psychological side of students; positive influence (learn to socialize, learn the characteristics of various people, students became diligently to come to school and more motivate to study if in good relation with their partner) and negative influence (tend to be a fragile person and lower the concentration if in fight with their partner). So, the researcher conclude that romance indirectly influence teaching and learning process. Therefore the researcher suggest that students should more focus on education to achieve the brilliant future and delay the romance activities until their psychological mature enough to accept all of the consequences of romance, so that undesireable things can be minimized.Key Words: teenager students, romance, psychologycal, teaching and learning process.Peneliti mengadakan penelitian yang bertujuan: 1) untuk mengetahui faktor-faktor yang menyebabkan siswa melakukan aktivitas percintaan, 2) untuk mengetahui pengaruh percintaan terhadap proses belajar mengajar. Subyek penelitian ini yaitu siswa semester ke tiga Universitas Gunung Rinjani Tahun Akademik 2017/2018. Penelitian ini menggunakan pendekatan kualitatif dimana data tersebut berupa hasil wawancara yang diperoleh peneliti terhadap beberapa responden setelah melakukan observasi. Untuk mengumpulkan data, peneliti menggunakan model analisis data Miles and Huberman yang terdiri dari reduksi data, presentasi data dan kesimpulan. Analisis data menunjukkan bahwa: 1) faktor yang menyebabkan pelajar melakukan hubungan percintaan yaitu: faktor internal terdiri dari lemahnya pembekalan dan pemahaman tentang agama, kelabilan masa remaja, dan faktor eksternal terdiri dari lingkungan dan teman yang buruk. 2) pengaruh percintaan terhadap psikologis pelajar: pengaruh positif (belajar bersosialisasi, belajar mengenal berbagai macam karakteristik orang, lebih rajin dan lebih termotivasi dalam hal belajar jika hubungan dengan pasangannya baik-baik saja), pengaruh negatif (cenderung menjadi pribadi yang rapuh dan menurunkan konsentrasi jika sedang bermasalah dengan pasangan). Jadi, secara tidak langsung percintaan sangat berpengaruh terhadap proses belajar mengajar. Oleh karena itu peneliti menyarankan agar pelajar lebih fokus terhadap pendidikan untuk menggapai masa depan yang gemilang dan menunda bercinta-cintaan sampai mental dan psikologis mereka cukup matang untuk menerima segala konsekuensi dari percintaan tersebut untuk meminimalisir segala sesuatu yang tidak dinginkan.Kata Kunci: siswa remaja, percintaan, psikologis, proses belajar mengajar.